Finding Lost & Found. Designer's Notes from the Process of Creating a Jewish Game for Learning - Gottlieb, Owen (Gamevironments, 2017)
This article provides context for and examines aspects of the design process of a game for learning. Lost & Found (2017a, 2017b) is a tabletop-to-mobile game series designed to teach medieval religious legal systems, beginning with Moses Maimonides' Mishneh Torah (1180), a cornerstone work of Jewish legal rabbinic literature. Through design narratives, the article demonstrates the complex design decisions faced by the team as they balance the needs of player engagement with learning goals. In the process the designers confront challenges in developing winstates and in working with complex resource management. The article provides insight into the pathways the team found through the challenges in the creation of the game.